THE TYPES OF ERRORS IN DESCRIPTIVE TEXT COMMITTED BY THE STUDENTS OF STMIK STIKOM INDONESIA - Ni Nyoman Ayu J. Sastaparamitha; Ni Made Lisma Martarini (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This study was focused on analyzing the types of errors in descriptive text committed by the students of STMIK STIKOM Indonesia. Descriptive qualitatively was chosen in this research which was done through an on-line observation. The students were assigning to write descriptive text through Google Classroom and the result was taken as the sample data. The obtained data were analyzed descriptively. The research finding shows six errors namely the topic sentence, the developing sentences, the coherence, the diction, the grammar, and the mechanics. Some errors are indefinite concerning to previous criteria. The outcome defines undeniability for the teacher to apply any methods to minimize errors in writing descriptive text. At the same time, the students should obtain knowledge about indicators and practice in writing descriptive text. Furthermore, the next researchers have to gain other preference in finding types of errors.